2003
DOI: 10.1152/ajpgi.00456.2002
|View full text |Cite
|
Sign up to set email alerts
|

Motilin effects on the proximal stomach in patients with functional dyspepsia and healthy volunteers

Abstract: This study investigates motilin effects on the proximal stomach in patients with functional dyspepsia (FD) and healthy volunteers. Eight healthy volunteers and 12 patients with FD were infused with synthetic motilin or placebo. Proximal gastric volume was measured with a barostat at constant pressure and during isobaric distensions. Abdominal symptoms were scored by visual analog scales. Plasma motilin concentrations were measured by radioimmunoassay. Motilin concentrations and baseline gastric volumes were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
3
22
0
1
Order By: Relevance
“…Efficacy in a subset of those patients with lower body mass index and hemoglobin A1C suggests a role in nondiabetics with upper gastrointestinal symptoms [176] . Motilin receptor agonists are known to decrease gastric accommodation and compliance [177,178] and are susceptible to tachyphylaxis, both factors that may contribute to limited efficacy in FD.…”
Section: Targeting Electromechanical Dysfunctionmentioning
confidence: 99%
“…Efficacy in a subset of those patients with lower body mass index and hemoglobin A1C suggests a role in nondiabetics with upper gastrointestinal symptoms [176] . Motilin receptor agonists are known to decrease gastric accommodation and compliance [177,178] and are susceptible to tachyphylaxis, both factors that may contribute to limited efficacy in FD.…”
Section: Targeting Electromechanical Dysfunctionmentioning
confidence: 99%
“…Furthermore, studies assessing the effect of erythromycin on gastric tone reported that administration of motilin or of erythromycin reduced meal-induced relaxation [100][101][102] , thereby enhancing sensitivity to gastric distention [103] . This adverse effect of erythromycin on gastric accommodation to a meal may contribute to its overall poor symptomatic response in patients with FD.…”
Section: Erythromycinmentioning
confidence: 99%
“…Bei Patienten mit funktioneller Dyspepsie ist die Wirkung von Erythromycin und anderen selektiven Motilinrezeptoragonisten auf die Symptomenintensität unzureichend. So zeigte sich nicht nur eine fehlende Überlegenheit gegenüber Plazebo, sondern eine signifikante Verschlechterung der epigastrischen Beschwerden [21,36]. Dies zeigt, dass die Beschleunigung der Magenentleerung nicht ausreicht, dyspeptische Symptome zu bessern.…”
Section: Erythromycinunclassified